Investigating the influence of RF power on the surface morphological and optical properties of sputtered TiO2 thin films - Grayeli, Alireza; Ahmadpourian, Azin; Jurečka, Stanislav; Luna, Carlos; Rezaee, Sahar; Karimi, Maryam (Optical materials, 2024)
Thin films of titanium dioxide (TiO2), with thicknesses ranging from 105 to 231 nm, were deposited on glass substrates using radio-frequency (RF) magnetron sputtering in an argon atmosphere at four distinct RF power levels: 40, 70, 100, and 130 W, with the deposition time kept constant. The crystalline structure, surface morphology and optical and semiconductor properties of the obtained films were analyzed using X-ray diffraction (XRD), Atomic Force Microscopy (AFM) and UV–visible transmittance spectroscopy. These analyses revealed that the crystallinity of the films improves with increasing RF power, corresponding to an increase in film thickness. Consequently, the samples transition from poorly crystalline or amorphous structure to a monocrystalline rutile phase with a (110) texture. However, at the highest RF power studied, this texture is partially disrupted by the formation of nanocrystals with different orientations. The surface roughness exhibited multifractal characteristics, with complexity systematically decreasing and surface stiffness reducing as RF power increased. Refractive indices and optical band gap energies were determined using the Swanepoel and Tauc plot methods, respectively. The films exhibited a notable increase in the refractive index and a decrease in the optical band gap, from 3.81 eV to 3.52 eV, as the RF power was increased. This underscores the influence of RF power on the optical and semiconductor properties of TiO2 films. [Display omitted] •TiO2 thin films were deposited on glass substrates using RF magnetron sputtering to study the impact of varying RF power on their properties.•Increasing RF power enhanced the crystallinity and modified the crystalline texture of the TiO2 thin films.•The films exhibited multifractal surface roughness, with complexity and surface stiffness decreasing systematically as RF power increased.•Refractive indices increased notably with increasing RF power, while the optical band gap energy decreased under the same conditions.